2015
DOI: 10.3109/13880209.2015.1033563
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of 2,7-dihydroxy-3-methylanthraquinone on human gastric cancer SGC-7901 cellsin vitroandin vivo

Abstract: Objective: The objective of this study is to study the anticancer effect and mechanism of DDMN on SGC-7901 cells. Materials and methods: The MTT assay was used to determine the effect of DDMN on cell viability of SGC-7901 cells, and the cytotoxic effect was evaluated by the IC 50 value. After treatment with different doses of DDMN (10, 20, and 40 mM) for 48 h, flow cytometry was used to investigate the apoptosis of SGC-7901 cells induced by DDMN. Further, western blotting was performed to study anticancer mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…26 Likewise, these findings are consistent with previous studies showing that chemotherapeutic sensitivity is enhanced by both rubimaillin and puerarin, which inhibit the expression of the mdr1 gene in breast cancer via the AMPK pathway. 30,31 Analogously, APS promotes glucose uptake in L6 myotubes through AMPK activation and, consequently, AS160/TBC1D4 phosphorylation. 24 However, it remains unclear whether APS regulates chemotherapeutic sensitivity of GC to adriamycin via the AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…26 Likewise, these findings are consistent with previous studies showing that chemotherapeutic sensitivity is enhanced by both rubimaillin and puerarin, which inhibit the expression of the mdr1 gene in breast cancer via the AMPK pathway. 30,31 Analogously, APS promotes glucose uptake in L6 myotubes through AMPK activation and, consequently, AS160/TBC1D4 phosphorylation. 24 However, it remains unclear whether APS regulates chemotherapeutic sensitivity of GC to adriamycin via the AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Xenograft is an accepted model for investigating the effects of anti-carcinogenic agents, as well as their underlying mechanisms [15,16]. The results obtained in the xenograft assay revealed that DHF exerted significant inhibition on the growth of tumor tissue induced by HepG2 cells by reductions in levels of Survivin and Bcl-2, upregulation of Bax, c-caspase-9 and c-caspase-3 expressions, and increases in cytoplasmic levels of Smac and cytochrome c ( Figures 6 -8).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the treatment duration, the animals were sacrificed and the tumor tissues were excised and subjected to western blot assay. Tumor volume (TV) was estimated as in Eq 2 [16].…”
Section: Xenograft Studiesmentioning
confidence: 99%
“…2, 7dihydroxy-3-methylanthraquinone (DDMN), a flavone isolated from Hedyotis diffusa Willd. Herba, induced caspase-dependent apoptosis of SGC-7901 gastric cancer cells [48]. 6, 7, 30-trimethoxy-3, 5, 40-trihydroxy flavone (TTF), extracted from Chrysosplenium nudicaule Ledeb.…”
Section: Apoptosis-inducing Natural Molecules In Gastric Cancermentioning
confidence: 99%
“…Wu et al revealed that phenolic alkaloids of Menispermum dauricum induced apoptosis and suppressed gastric tumor growth by inducing apoptosis and inhibiting oncogenic Kirsten Rat sarcoma viral oncogene homolog (K-RAS) expression [42]. Xenograft mice treated with trifolirhizin, DDMN or arsenic trioxide developed smaller tumors compared to the control group [44,48,69]. When BALB/C mice grafted with MFC mouse gas-tric cancer cells were treated curcumin solution every day for 60 days, expressions of interferon gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), granzyme B, and perforin were upregulated while differentiated embryonic chondrocyte gene 1 (DEC1), hypoxiainducible factor-1 alpha (HIF-1α), STAT3 and VEGF expressions were downregulated in the experimental group [71].…”
Section: Apoptosis-inducing Natural Molecules In Gastric Cancermentioning
confidence: 99%